Multidrug resistance protein-6 (MRP6) in human dermal fibroblasts. Comparison between cells from normal subjects and from Pseudoxanthoma elasticum patients - Boraldi, F.; Quaglino, D.; Croce, M.A.; Garcia Fernandez, M.I.; Tiozzo, R.; Gheduzzi, D.; Bacchelli, B.; Pasquali Ronchetti, I. (Matrix biology, 2003)
Multidrug resistance protein-6 (MRP6) is a membrane transporter whose deficiency leads to the connective tissue disorder Pseudoxanthoma elasticum (PXE). In vitro dermal fibroblasts from normal and PXE subjects, homozygous for the R1141X mutation, were compared for their ability to accumulate and to release fluorescent calcein, in the absence and in the presence of inhibitors and competitors of the MDR–multidrug resistance protein (MRP) systems, such as 3-(3-(2-(7-choro-2 quinolinyl) ethenyl)phenyl ((3-dimethyl amino-3-oxo-propyl)thio) methyl) propanoic acid (MK571), verapamil (VPL), vinblastine (VBL), chlorambucil (CHB), benzbromarone (BNZ) and indomethacin (IDM). In the absence of chemicals, calcein accumulation was significantly higher and the release significantly slower in PXE cells compared to controls. VBL and CHB reduced calcein release in both cell strains, without affecting the differences between PXE and control fibroblasts. VPL, BNZ and IDM consistently delayed calcein release from both control and PXE cells; moreover, they abolished the differences between normal and MRP6-deficient fibroblasts observed in the absence of chemicals. These findings suggest that VPL, BNZ and IDM interfere with MRP6-dependent calcein extrusion in in vitro human normal fibroblasts. Interestingly, MK571 almost completely abolished calcein release from PXE cells, whereas it induced a strong but less complete inhibition in control fibroblasts, suggesting that MRP6 is not inhibited by MK571. Data show that MRP6 is active in human fibroblasts, and that its sensitivity to inhibitors and competitors of MDR–MRPs’ membrane transporters is different from that of other translocators, namely, MRP1. It could be suggested that MRP1 and MRP6 transport different physiological substances and that MRP6 deficiency cannot be overcome by other membrane transporters, at least in fibroblasts. These data further support the hypothesis that MRP6 deficiency may be relevant for fibroblast metabolism and responsible for the metabolic alterations of these cells at the basis of connective tissue clinical manifestations of PXE.